Overview of Colonial Development Policy on Malayan pineapples industry, 1926-1934 - Mohd Shazwan Mokhtar; Mohd Samsudin; Suffian Mansor (Penerbit Universiti Kebangsaan Malaysia, 2021)
During the inter-war years, the Colonial Empire played a significant role in contributing tropical products to the United Kingdom. Besides supplying raw materials, the colonies also contribute to the food supply for the mother country's inhabitants. In 1925, the Imperial Economic Committee began promoting and inquiring the empire’s food product for consumption in the United Kingdom. Afterwards, the British government introduced the Colonial Development Act of 1929 to encourage tropical development in the Colonial Empire. However, the present study neglected the influence of that on Malayan economic activities. Thus, this article examines the implementation of the colonial development policy in promoting Malayan pineapples industry. This study used content analysis to construct the relationship between colonial policy and economic development in Malaya. This study provides historical evidence and data collected from the National Archives of the United Kingdom and Malaysia's National Archives. The findings showed that the imperial aid had supported Malaya in becoming a major supplier for canned pineapples in the British Empire. However, the colonial development policy led the colonial government in Malaya as the debtor to the imperial government.